Coeliac disease with autoimmune haemolytic anaemia. Issue 707 (September 1984) - Miller, D. G.
Abstract : Two patients are described who have developed autoimmune haemolytic anaemia in association with their coeliac disease. Autoimmune haemolytic anaemia may represent an extension of immunological disorders linked with coeliac disease, centred on the histocompatibility antigen B8.